Facial Emphysema following Closure of Oroantral Fistulae. (5th August 2021) - Nizar, Muhammad Aiman Mohd; Nabil, Syed
Abstract : Subcutaneous emphysema (SE) is a swelling which develops due to air entrapped underneath the subcutaneous tissue and facial planes causing distention of the overlying skin. SE can develop due to trauma, surgery, or infection. The diagnosis of SE is mostly based on clinical findings of crepitation upon palpation of the swelling. Once diagnosed, SE is usually managed by close observation and in some cases may require surgical decompression and antibiotic prophylaxis. We report a rare case of SE of the left malar which developed following closure of oroantral communication using the buccal fat pad.